Soldier in the Sinai : a general's account of the Yom Kippur war - Sakal, Emanuel (Foreign military studies., 2014)
In surprise attacks on Israel in October 1973, Egyptian and Syrian forces crossed ceasefire lines to enter the Israeli-held Sinai Peninsula and Golan Heights, igniting what became known as the Yom Kippur War. In the north, Israel succeeded in blocking the Syrian advance, but in the south, it failed to achieve an operational decision in the defense campaign. In Soldier in the Sinai, mobile and armored warfare expert Major General Emanuel Sakal analyzes the operational and strategic decisions made by Israel''s political and military leadership and assesses the causes of the defense''s first-phas.